Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 4√6 ;b = -13 ;c = -2√6


= 4√6.-2√6 = -48


And either of their sum or difference = b


= - 13


Thus the two terms are - 16 and 3


Difference = - 16 + 3 = - 13


Product = - 16.3 = - 48





(On using √6 = √3 √2 and 16 = 4.2.√2 √2 )


(4√2 x + √3)(√3 x-2√2) = 0


(4√2 x + √3) = 0 or (√3 x-2√2) = 0


x = (-√3)/(4√2 ) or x = (2√2)/√3


Roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics